Rehabilitation after Total Laryngectomy—A Tribute to the Pioneers of Voice Restoration in the Last Two Centuries - Lorenz, Kai J. (Frontiers in Medicine, 2017)
Background. The most severe consequence of laryngectomy for patients is the loss of their voice. For this reason, voice rehabilitation has been an integral aspect of treatment after total laryngectomy from the very beginning. A wide variety of different technical and surgical approaches are available and reflect the problems associated with the rehabilitation of communication and swallowing after the removal of the larynx. Methods. We used Internet search engines and libraries to conduct a search of the current medical literature and historical sources of medical information in order to identify and summarise landmark work on this subject. Discussion. Four types of methods have been used to restore the voices of patients, i.e. external devices, oesophageal speech, internal voice prostheses, and surgically created tracheo-oesophageal fistulas that do not involve the use of a prosthetic device.